Clinical characteristics of duodenal-type follicular lymphoma - Lu Wang; Wenyan Shen; Xiaoyuan Zhang; Ling Xue; Beili Hu (Discover Oncology)
Abstract Duodenal-Type Follicular Lymphoma (DFL) is a rare extranodular B-cell lymphoma, which mainly involves the duodenum. It typically affects middle-aged individuals and occurs equally in both genders. Common symptoms include upper abdominal discomfort, pain, indigestion, etc. Histopathologically, the condition is characterized by the disruption of follicular architecture, accompanied by the hyperplasia of central cells, and may optionally exhibit the “starry sky” phenomenon. The main treatment for DFL is observation and waiting due to the lack of symptoms and slow progression. The article reviews recent insights into DFL’s epidemiology, symptoms, treatment, and prognosis.